Anonymous Reflections of Art in Public Spaces; Examples From the World - Ardatürk, Ahmet Sadi (Street Art & Urban Creativity, 2022)
As identical and comparable with humanity's existence, art has existed in its own sphere or created a space for itself throughout history. These spaces represent oneness in private and individual spheres from time to time, while they sometimes mean oneness in a public space. Art is also precious and effective in public spaces as a reflection of culture and human discourse and action. This study tries to reveal this value based on examples from different cities and different countries and aims to examine drawing-based street art and graffiti existing in the public space with some concepts like culture, space, and experience. In line with this purpose, knowledge is produced basically from observation techniques and experience. The existence of the said works has been examined and photographed on site, some examples expressing the discourse have been selected from dozens of photographs, and then phenomenological information has been analyzed with literature information. Then knowledge has been sought to be produced. In this context, the uniting, experience-creating, space-creating, and life-forming effects of the work of art have been observed, and its relations with culture and practice have been examined. Then the meaning has been explored as independent of the criteria like identity and brand. As a different discourse, it is stated in this study that what constitutes the reality of drawing-based works of art and graffiti in the public space is neither the name written under each piece nor the capitalist economies and dominant political views but the social acceptance of the work, the relationship it establishes with culture and its meaning.